Quantifying cognitive and affective impacts of Quizlet on learning outcomes: a systematic review and comprehensive meta-analysis - Özdemir, Osman; Seçkin, Hümset (Frontiers in Psychology, 2024)
Background This study synthesizes research on the impact of Quizlet on learners’ vocabulary learning achievement, retention, and attitude. Quizlet’s implementation in language education is posited to enhance the learning experience by facilitating the efficient and engaging assimilation of new linguistic concepts. The study aims to determine the extent to which Quizlet influences vocabulary learning achievement, retention, and attitude. Methods Employing a meta-analysis approach, this study investigates the primary research question: “Does Quizlet affect students’ vocabulary learning achievement, learning retention, and attitude?” Data were collected from various databases, identifying 94 studies, of which 23 met the inclusion criteria. The coding reliability was established at 98%, indicating a high degree of agreement among experts. A combination of random and fixed effects models was used to analyze the effect size of Quizlet on each outcome variable. Results Quizlet was found to have a statistically significant impact on learners’ vocabulary learning achievement, retention, and attitude. Specifically, it showed moderate effects on vocabulary learning achievement (g = 0.62) and retention (g = 0.74), and a small effect on student attitude (g = 0.37). The adoption of the fixed effects model for attitude was due to homogeneous distribution, while the random effects model was used for achievement and retention because of heterogeneous distribution. Conclusion Quizlet enhances vocabulary learning achievement, retention, and has small positive effect on learner attitude. Its integration into language education curricula is recommended to leverage these benefits. Further research is encouraged to explore the optimization of Quizlet and similar platforms for educational success.